Elucidating Pathway and Anesthetic Mechanism of Action of Clove Oil Nanoformulations in Fish - Kantaporn Kheawfu; Surachai Pikulkaew; Petrine Wellendorph; Louise von Gersdorff Jørgensen; Thomas Rades; Anette Müllertz; Siriporn Okonogi (MDPI AG, 2022)
Clove oil (CO), an essential oil of Syzygium aromaticum, has been reported as an anesthetic for many fish species. However, its insoluble properties require a suitable delivery system for its application. In the present study, nanoformulations of CO as a nanoemulsion (CO-NE), a self-microemulsifying drug-delivery system (CO-SMEDDS), and a self-nanoemulsifying drug-delivery system (CO-SNEDDS) were prepared for delivering CO. Zebrafish were used as a fish model to investigate oil pathways. The result shows fluorescence spots of fluorescence-labeled CO accumulate on the gills, skin, and brain. All CO nanoformulations significantly increased penetration flux compared to CO ethanolic solution. Investigation of the anesthetic mechanism of action using a rat brain γ-aminobutyric acid subtype A (GABAA) receptor-binding test demonstrates that CO and its major compound, eugenol, modulate [3H]muscimol binding. CO-NE exhibited a concentration-dependent binding activity with an EC50 value of 175 µg/mL, significantly higher than CO solution in dimethyl sulfoxide. In conclusion, CO enters the fish through the skin and gills. The anesthetic mechanism of action of CO is based on modulation of [3H] muscimol binding to GABAA receptors. Among three nanoformulations tested, CO-NE is the most effective at increasing permeability and enhancing the receptor-binding activity of the oil.